Investigation of the Relationship between Eating Disorders and the Perception of Teasing in Adolescents - Yildiz, Yasin; Özmaden, Murat; Okudan, Bilal; Kızılca, Serkan (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the relationship between eating disorder in adolescents and perception of teasing. Methods: Four hundred-one (216 female, 185 male) high school students, who were preparing for university entrance exams, voluntarily participated in the study. A personal information form, an Eating Disorder rating scale, and Adolescent-Child Teasing Scale were used to collect the data. SPSS package program was used for data analysis. Skewness and kurtosis values were checked to determine whether the data showed normal distribution. In this context, it was determined that there was no extreme/outlier in the data, and Independent sample t-test, One-way ANOVA and Pearson Correlation analyzes were performed in the analysis of the data. Results: Statistically significant differences were found between the variables of gender, age, exercising and body mass index, and the perception of eating disorder and teasing. Moreover, it was observed that there was a statistically positive relationship between the eating disorder variable and the teasing variable. Conclusion: It was concluded that female students attach more importance to their physical and healthy lives, students who did not exercise had higher anxiety about being physically and teased. Besides, it was found that as the eating disorder level increased, the perception of teasing also increased.